Three phase pulse width modulation (PWM) inverter using PIC16F84A microcontroller / Ahmad Nizomuddean Jawan - Jawan, Ahmad Nizomuddean (2018)
Sinusoidal pulse width modulation (SPWM) technique is one of the PWM techniques that had been used to operate three phase inverter. It is used three sinusoidal wave displace in 120o phase difference as a reference signal for three phase inverter. This paper represents a three phase sinusoidal PWM power MOSFET inverter using PIC16F84A microcontroller with 700VA output power. The Sinusoidal PWM signal is generate using PIC16F84A microcontroller to control the switching period turning on and off of the power MOSFET. This paper also represents a three phase inverter circuit design and simulation using Proteus simulation software. Proteus simulation software is used to design a schematic circuit for three phase inverter and produce three phase sinusoidal waveform. Three phase power MOSFET inverter hardware is used to operate three phase induction motor with 200W rated power in 50Hz frequency. The inverter portion of the design consists of a power MOSFET, integrated gate drive, PIC microcontroller and additional related circuitry.